Immunostimulant Properties of Chemical Delivery Systems in Vaccine Development - Hosseinzadeh, Sahar; Bolhassani, Azam (Current Drug Delivery, 2015)
One approach to improve the vaccine quality is the incorporation of immunomodulators and/or adjuvants with modified delivery systems. The use of delivery systems especially chemical carriers is a promising strategy in the prevention and treatment of infections, cancers, allergies and autoimmune diseases. These systems are able to elicit an effective immune response as well as stability and safety in vaccine development. Synthetic microparticles, liposomes, chitosan, virus like particle, polymeric nanogel, phytosome, noisome, and micro/ nanospheres have been applied as carriers, providing a broad variety of immunomodulatory effects in vaccines. The potency and nature of immune responses rely on the physicochemical properties of the vaccine constructs (e.g., size and charge), the route of injection, the biochemical characteristics and the amount of antigen. Three main steps are necessary for vaccine efficiency such as targeting, activation and transfection/ antigen presentation. These systems can generally influence the type and direction of immune responses. This review describes different vaccine delivery systems developed to generate immunomodulatory effects.
Keywords: immunomodulatory effects